Incidental Finding of Arteria Lusoria - Chaymae Faraj MD; Sara Essetti MD; Kaoutar Maslouhi MD; Nazik Allali PhD; Siham El haddad PhD; Latifa Chat PhD (SAGE Publishing, 2024)
The arteria lusoria or retroesophageal right subclavian artery is the most common malformation of the aortic arch. It may be discovered with some symptoms of airway and/or esophageal compression, such as dyspnea or dysphagia, but in most cases it is an asymptomatic pathology. We report a case of a 3 months old patient diagnosed with Down syndrome who was admitted for pulmonary infection with incidental finding of retrooesophageal right subclavian artery.